Primary urachal signet ring cell carcinoma: A case report - Wang, Qing; Chen, Xiaolong; Zhang, Jianqing; Luo, Yuting; Jiang, Kehua (Frontiers in Oncology, 2022)
Urachal signet ring cell carcinoma is a kind of rare but aggressive tumor and few cases have reported previously. A 49-year-old male with primary complaints of increased frequency of urination, urodynia, and hematuria was diagnosed to be primary urachal signet ring cell carcinoma in our department. Multiple metastases were found in sigmoid colon, terminal ileum, mesentery, and peritoneum during operation and palliative surgery involving partial cystectomy with en bloc resection of the urachus was then performed. Chemotherapy regimen of fluorouracil combined with cisplatin was made for this case. In addition, this patient also received anlotinib for targeted therapy. As so far, this patient has done well on regular follow-up for 6 months and is in stable condition. We reported this additional urachal signet ring cell carcinoma case and conducted literature review to strengthen the cognition of this disease.